Targeting Reciprocally Connected Brain Regions Through CAV-2 Mediated Interventions - Morceau, Sarah; Piquet, Robin; Wolff, Mathieu; Parkes, Shauna L. (Frontiers in Molecular Neuroscience, 2019)
An important issue in contemporary neuroscience is to identify functional principles at play within neural circuits. The reciprocity of the connections between two distinct brain areas appears as an intriguing feature of some of these circuits. This organization has been viewed as “re-entry”, a process whereby two or more brain regions concurrently stimulate and are stimulated by each other, thus supporting the synchronization of neural firing required for rapid neural integration. However, until relatively recently, it was not possible to provide a comprehensive functional assessment of such reciprocal pathways. In this Brief Research Report, we highlight the use of a chemogenetic strategy to target projection-defined neurons in reciprocally connected areas through CAV-2 mediated interventions in the rat. Specifically, we targeted the bidirectional pathways between the dorsomedial prefrontal cortex and the mediodorsal thalamus, as well as those connecting the insular cortex and the basolateral complex of the amygdala. These data showcase the usefulness of CAV-2-related strategies to address circuit-level issues. Moreover, we illustrate the inherent limitation of Cre-dependent AAVs with ‘leaked’ expression of the gene of interest in the absence of Cre and highlight the need for appropriate control conditions.